-6(6x-1)=-36x-6

Simple and best practice solution for -6(6x-1)=-36x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(6x-1)=-36x-6 equation:


Simplifying
-6(6x + -1) = -36x + -6

Reorder the terms:
-6(-1 + 6x) = -36x + -6
(-1 * -6 + 6x * -6) = -36x + -6
(6 + -36x) = -36x + -6

Reorder the terms:
6 + -36x = -6 + -36x

Add '36x' to each side of the equation.
6 + -36x + 36x = -6 + -36x + 36x

Combine like terms: -36x + 36x = 0
6 + 0 = -6 + -36x + 36x
6 = -6 + -36x + 36x

Combine like terms: -36x + 36x = 0
6 = -6 + 0
6 = -6

Solving
6 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 144x^2-1/4=0 | | y-9=-1(x-16) | | 50-2x=15+3x | | 14(v+4)-2v=3(4v+4)-18 | | y-9=-0.66(x-16) | | y-9=-(2)/(3)(x-16) | | y-9=-2/3(x-16) | | 3x-208=x/9 | | 5(x+7)=-30(x+2) | | -5(x+4)+3x+5=5x+12 | | -7(x+3)+3x+7=5x+11 | | ((d-4)/(4))^(2)=64 | | 1/3*6h=20 | | -3(2x+5)=7x+1 | | 7(x-7)+2=9-(x+6) | | 3(x-3)=2-8x | | x-3=.75(2-x)+6 | | 2h-3h=15 | | X/0.4=11.25 | | 11x^2=44x | | 5x/x=(8x^3)/x^2 | | Y-4=-8.4 | | lnx^2+3x-1=0 | | -(-2n-5)=-13-n | | 2(3*-4)=22 | | x11/20*30 | | x=11/30x230 | | 4k-5=6k+1 | | 5(m-4)=2m+3 | | -2(z-11/5)=3z | | 2x^2-6x-9=89 | | 18=-8x+6x |

Equations solver categories